Empowering Papalele Women Through the “SIPIKANSERI” Website: Digital Transformation to Increase Market Share of Fishing Business - Gainau, Paskanova Christi; Kilay, Trisye Natalia; Ruban , Angela; Pocerattu, Joshua Stevanus; Salakory, Vilencia Christin; Gainau, Kharisna Ezra Alfredo; Sipahelut, Teofillio Endrico; Lodiay, Ivan Marko; Samallo, Jacobus Robert; de Fretes, Vicky (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: This community service addresses the economic challenges faced by fishermen, who are highly dependent on unpredictable sea conditions, leading to difficulties in controlling operational costs and predicting sales. The program specifically focuses on empowering the women fish sellers (Papalele) in the community by introducing digital tools to enhance market access and sales efficiency. Purpose of the Study: The aim is to train Papalele women to utilize the SIPIKANSERI website for selling fish. The objectives are to improve their digital literacy, increase sales efficiency, expand their market reach, and ultimately contribute to the economic empowerment of the fishing community. Methods: The program employed a Participatory Action Research (PAR) approach, structured into four sequential stages: socialization, training, mentoring/assistance, and evaluation. Results: The activity yielded positive outcomes: 1) Post-training assessments showed an improved understanding of the website among participants. 2) Post-mentoring evaluations indicated an increased practical ability to operate key website features, though initial adoption was modest (3 out of 25 trained members actively utilized the platform). 3) The program led to increased efficiency and empowerment, with users saving on selling time, consumption costs, and product unloading costs. 4) It successfully expanded the market reach, attracting customers from various areas such as Passo, Lateri, and Gunung Nona.